2022
DOI: 10.1007/s00125-022-05741-2
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical variable-based cluster analysis identifies novel subgroups with a distinct genetic signature, lipidomic pattern and cardio-renal risks in Asian patients with recent-onset type 2 diabetes

Abstract: Aims/hypothesis We sought to subtype South East Asian patients with type 2 diabetes by de novo cluster analysis on clinical variables, and to determine whether the novel subgroups carry distinct genetic and lipidomic features as well as differential cardio-renal risks. Methods Analysis by k-means algorithm was performed in 687 participants with recent-onset diabetes in Singapore. Genetic risk for beta cell dysfunction was assessed by polygenic risk score. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Due to the elevated risk of mortality with these diseases, there is a need for strategies in its identification, prevention, and treatment within healthcare. In 2022, as evidenced in Figure 5, the bulk of research articles focussed on related diseases: CVD, 232–255 diabetes, 166,233,249,250,256–278 liver disease, 51,279–293 MetS 277,294,295 and obesity 277,295–305 …”
Section: In Review: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the elevated risk of mortality with these diseases, there is a need for strategies in its identification, prevention, and treatment within healthcare. In 2022, as evidenced in Figure 5, the bulk of research articles focussed on related diseases: CVD, 232–255 diabetes, 166,233,249,250,256–278 liver disease, 51,279–293 MetS 277,294,295 and obesity 277,295–305 …”
Section: In Review: Results and Discussionmentioning
confidence: 99%
“…Bibliometric analyses of clinical lipidomics publications in 2022 using Scopus search terms “lipidomics” AND “clinic*” on 15 th December 2022 …”
Section: In Review: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ANDIS clusters have been replicated in several populations, a study in a Singaporean cohort highlights the impact of certain ethnicities on disease profile and progression and the importance of testing the metabotyping model in the target population before considering its application (44) . Using the same ANDIS method and markers (except for glutamate decarboxylase antibody that determined autoimmune diabetes), a total of three clusters were reported.…”
Section: Potential Of Metabotyping To Personalise Healthcare Illustra...mentioning
confidence: 99%
“…The design of the present study, and many of those in which only glycaemic trajectory groups have been identified, 1 was different from those in which distinct clusters of people with subtypes of adult-onset diabetes have been proposed. 29,30 In these latter studies, apart from not using HbA1c trajectories in the categorization process, only newly 29 or recently diagnosed 30 participants were included, the subgroups were based on multiple clinical/laboratory variables and endpoints that included biochemical and genetic tests that may not be available in routine clinical care, and follow-up was limited to ≤8 years.…”
Section: Associates Of Trajectory Subgroup Membershipmentioning
confidence: 99%